Analisis Dinamika Motivasi Kerja pada Guru Non-Formal dalam Perspektif Self-Determination Theory: A Systematic Literature Review - Rohmah, Iffah Hidayatur; Izzati, Umi Anugerah (Universitas Muhammadiyah Magelang, 2026)
This study aims to analyze the dynamics of work motivation among non-formal teachers, focusing on the intrinsic and extrinsic factors that influence their motivation and performance. The method used is a systematic literature review (SLR), which examines relevant articles from various sources related to the work motivation of non-formal teachers. The results of the study indicate that intrinsic motivation, such as satisfaction in teaching and the feeling of contributing to the development of students, plays a major role in increasing the commitment and teaching quality of non-formal teachers. Extrinsic motivation, such as awards and incentives, also provides additional encouragement, although in the long term, its influence is more limited. Leadership that supports teacher autonomy, work experience, and social support among colleagues were found to play an important role in strengthening teacher work motivation. Psychological factors, including emotional regulation, also play a role in maintaining motivation even when faced with stress. This study makes an important contribution to understanding the dynamics of non-formal teachers' work motivation and its implications for non-formal education management.